Direct diverticular peroral endoscopic myotomy for the treatment of thoracic esophageal diverticula: technique and outcomes - Gauci, Julia L.; Gupta, Sunil; Abu Arisha, Muhammad; Tang, Andrew; O’Sullivan, Timothy; Whitfield, Anthony; Cronin, Oliver; Perananthan, Varan; Kerrison, Clarence; Lee, Eric Y.; Burgess, Nicholas G.; Bourke, Michael J. (Endoscopy, 2023)
Background Diverticular peroral endoscopic myotomy (POEM) is an alternative to surgery for the management of symptomatic thoracic esophageal diverticula. Conventionally, this requires proximal tunnel formation but a direct approach may simplify the technique. Herein, we report the outcomes of direct diverticular-POEM (DD-POEM).Methods We conducted a single-center prospective observational study evaluating DD-POEM. This involved a direct approach to the diverticulum. Success was defined as an Eckardt score of ≤ 3 without the need for reintervention.Results 10 patients underwent DD-POEM (median age 72 years; interquartile range [IQR] 14.3; male 60 % [n = 6]). Median diverticulum size was 40 mm (IQR 7.5) and median location was 35 cm from the incisors (IQR 8.3). Five patients (50 %) had an underlying dysmotility disorder. The median procedure duration was 60 minutes (IQR 28.8). There were no adverse events. The median hospital stay was 1 day (IQR 0.75). The pre-procedure median Eckardt score of 6 (IQR 4) significantly improved to 0 (IQR 0.75; P < 0.001) at a median follow-up of 14.5 months (IQR 13.8). Success was achieved in all patients.Conclusions DD-POEM was a safe technique for the management of thoracic esophageal diverticula. Owing to its simplicity and excellent performance it should be further evaluated for the treatment of this disorder.